MAKNA SEMANTIK KONTEKS SOSIAL EKONOMI CERPEN “HAWA PANAS” KARYA SILVERSTER PETARA HURIT - Pilipus Wai Lawet Lawet; Karolinda Letek Karhi (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2025)
This article aims to describe the semantic meaning of the socio-economic context of the short story "Hawa Panas" by Silverster Petara Hurit. The method used is a qualitative descriptive method. The study was conducted using a lexical and contextual semantic approach. The results of the study of the Semantic Meaning of the Socio-Economic Context of the Short Story "Hawa Panas" by Silverster Petara Hurit, as follows (1) the semantic meaning of the context of economic monopoly, the existence of monopoly and collusion, and local oligarchy, (2) the semantic meaning of the context of unfulfilled political promises, the existence of political manipulation, and empty promise politics, (3) the semantic meaning of the context of power ambition, the existence of gender inequality and exploitation of the power system, the existence of a gap between the elite and the common people, and (4) the semantic meaning of the context of market manipulation, the existence of actions to suppress market prices, hidden loan sharks, and misleading credit systems.